Konstruksi Atas Pemberitaan Bom Bunuh Diri di Medan pada Okezone.com (Analisis Framing Entman) - Marcelline Sastraminata; Nani Kurniasari (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2022)
Suicide bombings are a frequent act in Indonesia. The purpose of this study aims to find out the okezone point of view as a news writer on the news of suicide bombings that occurred in Medan. This study uses the paradigm of constructivism to understand construction and assess the point of view of researchers. This research uses a qualitative approach with a descriptive research type. The media text analysis method is used in this research to analyze the content of the message and spread the results of the research in detail. Using Robert Entman's framing analysis we know that this case is a case of terrorism resulting from a false understanding of religion. The result of this study is known that Okezone as a news writer stated that the suicide bombing in Medan was an act of terrorism. This terrorism exists because of the radicalism movement that wants change by using violence to turnradicalism into terrorism.